ЄВРОПОЦЕНТРИЗМ: ДО ПИТАННЯ ПРО ПРИЧИНИ ТА УМОВИ ВИНИКНЕННЯ (Zaporizhzhia Historical Review, 2021)
The study of eurocentrism is considered to be of great importance for comprehension of the dominant role of Europe in the world during Modern history period. The author focused upon analysis of the reasons and conditions of origin of given phenomenon in works of such famous scholars as Max Weber, Paul Kennedy and others.